Complexo de inclusão furazolidona: ciclodextrinas visando o desenvolvimento de medicamentos para o tratamento da Leishmaniose cutânea canina: : $b caracterização física e avaliação biológica in vitro - Carvalho, Suzana Gonçalves (2019)
Cutaneous leishmaniasis is an infectious disease that affects animals and humans, being caused by protozoa of the genus Leishmania. Canine cutaneous leishmaniasis (CCL) is considered an anthropozoonosis and, currently, there is no pharmacotherapy available in Brazil for its treatment. Thus, the search for pharmaceutical alternatives for use in animals has been subject of numerous researches. In this sense, the leishmanicidal activity of furazolidone has been studied by several authors and, since the drug is not used in the treatment of human leishmaniasis, its use for the treatment of CCL can be considered. Reports in literature point to furazolidone as a chemotherapeutic with good leishmanicidal activity. However, animal toxicity problems are also reported, which may be related to their low solubility and high doses required for the therapeutic effect to be achieved. Among the numerous pharmacotechnical alternatives available to overcome solubility problems, the formation of inclusion complexes with cyclodextrins deserves attention. In addition to improving the solubility and bioavailability of the guest molecules, the formation of inclusion complexes (ICs) may increase stability and favor the masking of the flavor of the drugs. In this context, the objective of the present work was to prepare ICs between furazolidone (FZD) and two cyclodextrins of pharmaceutical interest: ß-cyclodextrin (ßCD) and hydroxy-propyl-ß-cyclodextrin (HPßCD). The ICs were prepared in 1: 1 and 1: 2 molar ratios (FZD: CD) by the malaxation and lyophilization methods. The presence of amorphization of the particles and the success of the complexation were confirmed using complementary techniques, namely differential scanning calorimetry (DSC), thermogravimetry (TG / DTG), scanning electron microscopy (SEM), X-ray diffraction (XRD) Raman spectroscopy and solid state 13C nuclear magnetic resonance (NMR). Following the physical-chemical characterization, 50% growth inhibition of the promastigote forms by the resazurin method and the cytotoxicity on THP-1 9 macrophages by the MTT method in the 72-hour period were investigated. The malaxation and lyophilization processes chosen to obtain the complexes were shown to be simple and easy to perform, and could be used both in laboratory and industrial scale. The presence of amorphization and the indication of complexation for the products obtained from ß-CD and HP-ß-CD, in the molar ratio 1: 2, prepared by lyophilization, was confirmed by all the techniques used. In all other products, interactions between the drug and the cyclodextrins were observed, indicating the formation of non-complex type aggregates. All samples showed leishmanicidal activity and were non-toxic to THP-1 macrophages. The IC 50 values for the complexing products MHFZD1: 2 and LHFZD1: 2 were 2.7 and 3.02 µg / mL, respectively, both being considered promising for the development of veterinary drugs for the use in the treatment of leiomyoses in dogs.